PEMBUATAN GAME 2D RHYTHM RUNNING “CATCH THE BEAT” PADA PLATFORM ANDROID - Grandy Grandy; Jeanny Pragantha; Darius Andana Haris (Fakultas Teknologi Informasi Universitas Tarumanagara, 2021)
The game is developed using Unity Game Engine and C# language as a script maker. The game consist of 15 music with 4 music genres. The concept of this game is that the player must complete the stage containing various obstacles that can be passed or destroyed according to music’s beat and tempo. Touchscreen is used to control the game. The test results show that the game